Micropollutant abatement with UV/H2O2 oxidation or low-pressure reverse osmosis? A comparative life cycle assessment for drinking water production. (15th February 2022) - Roth, Christine; Wünsch, Robin; Dinkel, Fredy; Hugi, Christoph; Wülser, Richard; Antes, Ralf; Thomann, Michael
Abstract: Micropollutants (MP) are undesired in drinking water. Advanced oxidation processes (AOP) or low-pressure reverse osmosis membrane filtrations (LPRO) can be used to remove them during the water purification process. For a specific case, two treatment scenarios were compared with a life cycle assessment (LCA), using three impact assessment methods (Ecological Scarcity 2013, ILCD 2011, EDIP 2003). Scenario 1 (AOP-based) was a UV/H2 O2 oxidation with a subsequent granular activated carbon (GAC) filter to remove excess H2 O2 before soil infiltration. Scenario 2 (LPRO-based) was a side-stream treatment with an ultrafiltration (UF) and low-pressure reverse osmosis (LPRO) filtration before soil infiltration and the LPRO retentate was treated with O3 /H2 O2 and subsequent granular activated carbon (GAC) filter before discharge back into Rhine. Sensitivity analyses were performed on the relevant contributors to evaluate the robustness of the results. LCA results showed that in the base-line scenario (electricity from renewable energy sources) the LPRO-based treatment had notably fewer environmental impacts than the AOP-based treatment, which was confirmed with three impact assessment methods. Key contributors to the impacts were mostly operating resources, i.e., electricity, H2 O2, liquid O2 for ozone generation and GAC, but also construction resources in the LPRO process. The electrical energy source was decisive for the results: with a share of renewable energy sources <80%, the AOP-based treatment was the better option due to its lower specific energy demand. The optimization of treatment conditions, such as lower H2 O2 concentration at an increased UV fluence; different H2 O2 :O3 molar ratios; or extended GAC utilization time could influence the environmental impact within a range of ±10–30%. Environmental benefits, i.e. the reduction of potential hazardous effects of 21 MPs, were determined with EDIP 2003 and USEtox for both treatment scenarios. The estimated benefits were negligible in comparison to the environmental burden caused by the treatments, thus would not be justified from a global LCA impact-benefit perspective. However, because of several uncertainties and lack of data, the inclusion of treatment benefits in LCAs for drinking water purification requires further research. Graphical abstract: Image 1 Highlights: Systematic example of advanced treatment LCA in the drinking water sector. Robust LCA results with three impact assessment methods. Operating resources accounted for 70–94% of environmental impact on average. Energy source and treatment parameters significantly influenced the results. Environmental benefits from micropollutant abatement were negligible.